Eulophidae novae germanicae (Hymenoptera: Chalcidoidea). - Erdös, József (Beiträge zur Entomologie = Contributions to Entomology, 1956)
Nomenklatorische HandlungenHalochariessa Erdös, 1956 (Eulophidae), gen. n.germanica Erdös, 1956 (Halochariessa), spec. n.pannonica Erdös, 1956 (Halochariessa), spec. n.